Organizational commitment and work involvement on employee work agility in the restructuring condition - Widodo, Teguh; Riani, Asri Laksmi; Wening, Nur; Saifuddiin, Muhammad Rizqi (Interdisciplinary Social Studies, 2023)
In order to increase the productivity of the sugar business performance as well as assist the Government in realizing national sugar self-sufficiency, PT. XYZ restructured the sugar business. The business restructuring will certainly bring about significant changes in each business area, including organizational changes. The condition of business restructuring requires employees to be adaptive, resilient and proactive or in other words have good workforce agility. In addition, employees' organizational commitment and employees' job involvement in business restructuring conditions are a key variable for the business restructuring process to be successful. For this reason, this study aims to determine the effect of these two variables on employee work agility. The method used is a survey method by distributing three scales (OCQ, JIS, and WAS) online to research participants who are Management Employees of PT. XYZ working in Sugar Commodity. The analysis used in this research is a quantitative method using simple regression analysis. The results of this study indicate that first, there is a significant and positive effect of organizational commitment on workforce agility as evidenced by the t-value of 8.818 and a significance of 0.000. Second, job involvement also has a significant and positive effect on workforce agility as evidenced by the t-value of 10.399 and a significance of 0.000. Third, from the calculation of the coefficient of determination, it can be concluded that organizational commitment and job involvement have the influence on workforce agility of 29.1% and 36.4%, respectively.